Hearing-aid-processed Tone Pips: Electroacoustic and ABR Characteristics - Brown, Eugene; Klein, Alan J.; Snydee, Kimberly A. (Journal of the American Academy of Audiology, 1999)
The auditory brainstem response (ABR) recorded while wearing a hearing aid may supply supplemental information about the benefit and appropriateness of the hearing aid for certain infants. The purposes of this study were (1) to determine the effects of different output limiting circuits on the acoustics of tone-pip stimuli used for ABR recordings and (2) assess how changes in hearing-aid-processed stimuli affect ABR characteristics. Electroacoustic input/output functions to tone-pip stimuli were constructed for three different output limiting circuits (wide dynamic range compression, output compression, and linear with peak clipping) available in a programmable hearing aid. Wave V latency and amplitude functions were then measured to the same stimuli and hearing aid settings in five normal-hearing adults. Electroacoustic results showed that none of the output limiting circuits, including linear peak clipping, were effectively activated by tone pips compared to the hearing aid performance to continuous tones. Aided wave V latency and amplitude functions were asymptotic to high stimulus levels, suggesting that cochlear output was in saturation.Abbreviations: ABR = auditory brainstem response, I/O = input/output, MPO = maximum power output, OAE = otoacoustic emission, pe SPL = peak equivalent sound pressure level, SC = super compression, sPC = soft peak clipping, WDRC = wide dynamic range compression
Keywords: Auditory brainstem response; hearing aids